DETERMINING SHORT-TERM ORAL ANTIBIOTICS NON-ADHERENCE AND EXPLORING ITS ASSOCIATED FACTORS AMONG ORANG ASLI POPULATIONS AT KAMPUNG SUNGAI TONGGANG, IPOH, PERAK, MALAYSIA - DARREN KAR WING LAI; YEN PING NG; JIN YI CHOO; SHU YING LOOI; JING NG; BOON SENG TAN; CHENG HOON YAP; KWOK WEN NG (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objectives: This study aimed to determine the prevalence of non-adherence to short-term oral antibiotics among the Orang Asli community in Kampung Sungai Tonggang, Ipoh, Perak, Malaysia. Additionally, it explored the factors contributing to non-adherence and assessed the community’s knowledge and attitudes toward antibiotic use. Methods: A cross-sectional study was conducted among Orang Asli individuals prescribed short-term oral antibiotics. Data were collected through structured interviews, and adherence levels were assessed. Factors associated with non-adherence were analyzed using simple logistic regression. Knowledge and attitudes toward antibiotics were evaluated using a scoring system, with comparisons made based on demographic variables. Results: The findings revealed that 71.2% of respondents were non-adherent to their antibiotic regimen. Age and gender were significant factors influencing adherence, with male respondents being less likely to adhere (OR: 0.117, 95% CI: 0.02–0.60, p = 0.010). Knowledge and attitudes toward antibiotic use varied, with 50% of respondents demonstrating good knowledge (K-score ≥13). Literacy status and occupation significantly influenced knowledge levels (p < 0.05). Conclusion: Non-adherence to short-term oral antibiotics is prevalent among the Orang Asli community, with demographic and knowledge-related factors playing a role. Targeted educational interventions and culturally appropriate strategies are needed to improve adherence and ensure effective antibiotic use in this population.